The Negative Effects of Feces-Associated Microorganisms on the Fitness of the Stored Product Mite Tyrophagus putrescentiae - Green, Stefan J.; Nesvorna, Marta; Hubert, Jan (Frontiers in Microbiology, 2022)
Feces have been suggested as a major source of microorganisms for recolonization of the gut of stored product mites via coprophagy. The mites can host microorganisms that decrease their fitness, but their transmission is not known. To address the role of fecal microbiota on mite fitness, we performed an experimental study in which the surfaces of mite (Tyrophagus putrescentiae) eggs were sterilized. Mites eggs (15 per experimental box) were then hatched and grown on feedstock with and without feces. These experiments were conducted with four distinct T. putrescentiae populations (5L, 5K, 5N and 5P), and mite population density after 21 day of cultivation was used to assess mite fitness and the impact of fecal microbiota on fitness. Population density was not affected by the presence of feces in two of the cultures (5L and 5K), while significant effects of feces were observed in the other cultures (5N and 5P). Mite culture microbial communities were analyzed using cultivation-independent next-generation amplicon sequencing of microbial 16S and 18S ribosomal RNA (rRNA) genes in the fitness influenced populations (5N and 5P). Several microbial taxa were associated with fecal treatments and reduced mite fitness, including Staphylococcus and Bartonella-like bacteria, and the fungal genera Yamadazyma, Candida, and Aspergillus. Although coprophagy is the transmission route mites used to obtain beneficial gut bacteria such as Bartonella-like organisms, the results of this study demonstrate that fecal-associated microorganisms can have negative effects on some populations of T. putrescentiae fitness, and this may counteract the positive effects of gut symbiont acquisition.